2018
DOI: 10.1155/2018/1073687
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anticancer Roles of a Novel Strain ofBacillus anthracisIsolated from Vermicompost Prepared from Paper Mill Sludge

Abstract: Mass production of vermicompost using suitable species of earthworms and selecting target organic waste materials has appeared to be a great development in the realm of biotechnological research for the sustainable eco-management. Although, for the bioconversion of organic wastes to vermicompost, suitable earthworm species play major roles, a hoard of bacterial assemblages by virtue of production of different enzymes facilitate the process of vermicomposting. The present study has documented the roles of vermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In agreement with some earlier studies on some microbial extracts, the results clearly indicated that the crude extract of Halomonas sp. HA1 showed a significant anticancer effect on HepG2 cells associated with decreased viability and morphological alterations of the treated cells leading eventually to cell death 29,30,38 . To investigate the pro-apoptotic pathway of H. HA1 bacterial extract, the changes in apoptosis regulatory genes upon applying the extract on HepG2 cells were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with some earlier studies on some microbial extracts, the results clearly indicated that the crude extract of Halomonas sp. HA1 showed a significant anticancer effect on HepG2 cells associated with decreased viability and morphological alterations of the treated cells leading eventually to cell death 29,30,38 . To investigate the pro-apoptotic pathway of H. HA1 bacterial extract, the changes in apoptosis regulatory genes upon applying the extract on HepG2 cells were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Two kilograms from each sample were properly sundried and mixed with cow dung and straw in a ratio of 5:4:1. Owing to the toxicity of sludge, samples were supplemented with cow dung which act as a bulking agent in ceramic tubs (24 inch × 18 inch×18inch) along with thirty potential breeders of Perionyx excavatus for 60 days in three replicates (Ganguly et al., 2018). During the process of composting, the temperature was kept at 25 °C, pH (7.4–7.6) and moisture content of 60% through spreading of water at regular intervals (Ganguly and Chakraborty, 2018; Chanda et al., 2010).…”
Section: Methodsmentioning
confidence: 99%
“…According to Fernandes (2015) [26], the IS value for a compound to be considered safe must be greater than 1, however, to be considered significant as an anti-tumor compound, this index must be greater than 2. Ganguly et al (2018) [27] reported in their work a strong cytotoxic activity of Bacillus anthracis extracts against cancer cells with IC50 values of 64.5μg/mL. The CV26BM40H extract (Figure 4) was cytotoxic with IC50 from 100 μg/mL, but with similar cell viability for two strains, both for the tumor (B16F10) and non-tumor (3T3).…”
Section: Anti-tumor Testsmentioning
confidence: 86%